Toward improved endoscopic surveillance with multidiameter single fiber reflectance spectroscopy in patients with Barrett's esophagus. Issue 4 (31st January 2021) - Post, Anouk L.; de Groof, Albert J.; Zhang, Xu U.; Swager, Anne‐Fré; Fockens, Kiki N.; Pouw, Roos E.; Weusten, Bas L. A. M.; Faber, Dirk J.; de Bruin, Daniel M.; Bergman, Jacques J. G. H. M.; van Leeuwen, Ton G.; Sterenborg, Henricus J. C. M.; et al.
Abstract: Patients with Barrett's esophagus are at an increased risk to develop esophageal cancer and, therefore, undergo regular endoscopic surveillance. Early detection of neoplasia enables endoscopic treatment, which improves outcomes. However, early Barrett's neoplasia is easily missed during endoscopic surveillance. This study investigates multidiameter single fiber reflectance spectroscopy (MDSFR) to improve Barrett's surveillance. Based on the concept of field cancerization, it may be possible to identify the presence of a neoplastic lesion from measurements elsewhere in the esophagus or even the oral cavity. In this study, MDSFR measurements are performed on non‐dysplastic Barrett's mucosa, squamous mucosa, oral mucosa, and the neoplastic lesion (if present). Based on logistic regression analysis on the scattering parameters measured by MDSFR, a classifier is developed that can predict the presence of neoplasia elsewhere in the Barrett's segment from measurements on the non‐dysplastic Barrett's mucosa (sensitivity 91%, specificity 71%, AUC = 0.77). Classifiers obtained from logistic regression analysis for the squamous and oral mucosa do not result in an AUC significantly different from 0.5. Abstract : Early Barrett's neoplasia is easily missed during endoscopy. Based on the concept of field cancerization, it may be possible to identify the presence of a neoplastic lesion from measurements elsewhere in the esophagus or even the oral cavity. This study concludes that Single Fiber Reflectance spectroscopy can predict the presence of neoplasia elsewhere in the Barrett's segment based on measurements on the non‐dysplastic Barrett's mucosa.